A plain X-ray vascular calcification score is associated with arterial stiffness and mortality in dialysis patients - Adragao, T.; Pires, A.; Birne, R.; Curto, J. D.; Lucas, C.; Gonçalves, M.; Negrão, A. P. (Nephrology Dialysis and Transplantation, 2009)
Background. Vascular calcifications are highly prevalent in dialysis patients and are associated with arterial stiffness and mortality. The use of simple and inexpensive methods to evaluate arterial stiffness and vascular calcifications is desired. The objective of this study was to evaluate the relationship of a simple vascular calcification score (SVCS) with pulse wave velocity (PWV) and pulse pressure (PP) and to evaluate their association with all-cause mortality. Methods. 101 haemodialysis patients (71 men; 19% diabetic) were evaluated. At baseline, arterial stiffness was measured by PP and by PWV with Complior. SVCS was evaluated in plain X-ray of pelvis and hands. Results. During a 43-month observational period, 31 patients died. By Kaplan–Meier analysis, SVCS >3 ( P = 0.001), PP > 70 mmHg ( P = 0.001) and PWV > 10.5 m/s ( P < 0.001) were found to be associated with lower cumulative survival. Adjusting for multiple variables, association with mortality was maintained for SVCS >3 (HR = 3.308, P = 0.032) and PP > 70 mmHg (HR = 3.227, P = 0.031) in all patients and for PWV > 10.5 m/s (HR = 2.981, P = 0.047) in non-diabetic patients. Age ( P < 0.001), systolic pressure ( P = 0.004) and SVCS > 3 ( P = 0.032) were associated with PWV. Diabetes ( P = 0.031), calcium carbonate dose ( P = 0.009) and SVCS > 3 ( P = 0.012) were associated with PP. Conclusion. Higher SVCS, PWV and PP were associated with higher mortality in this population. SVCS was associated with arterial stiffness. Simple and inexpensive methods such as PP or SVCS may be used to detect mortality risk and to provide important information that may be relevant for guiding therapeutic intervention in dialysis patients.